UJI AKTIVITAS ANTIOKSIDAN EKSTRAK BIJI DAN KULIT BUAH MELINJO (Gnetum gnemon L.) - Dela Rosa (Universitas Pelita Harapan, 2020)
Melinjo (Gnetum gnemon L.), widely cultivated in Southeast Asia, is known to have many phenolic and flavonoid compounds which have antioxidant activity. Antioxidants such as phenolic and flavonoids have photoprotective capabilities because they can help inhibit the formation of free radicals. In this research, seed and skin of melinjo were extracted using various solvents, such as hexane, ethyl acetate, and ethanol. Antioxidant activity test using DPPH, total flavonoid, and total phenolic content were tested for each fraction. The result showed that ethanol fraction of melinjo seed has the best antioxidant activity both for the seed and the skin. IC50 for ethanol fraction from skin is 440,58 ± 40,89 ppm with total flavonoid and phenolic content are 145,00 ± 23,79 QE/ g DW dan 32,31 ± 4,03 mg QE/ g DW. Meanwhile IC50 for ethanol fraction from seed is 424,78 ± 10,30 ppm with total flavonoid and phenolic content is 172,57 ± 18,01 mg QE/ g DW dan 32,31 ± 4,03 mg QE/ g DW.